Physical Education by Improving Students' Interpersonal Communication Skills - Eko Purnomo; Eddy Marheni; Afrizal S; Agus Gumilar; Nina Jermaina; Nor Eeza Zainal Abidin (OVS LLC, 2024)
Background. Interpersonal communication skills have a significant influence that must be emphasized on the implementation of learning at school. Consequently, ongoing evaluation of students is essential to achieve optimal interpersonal communication skills. Objectives. This study aimed to examine the impact of implementing physical education on interpersonal communication skills in Senior High School (SMA) and Vocational School (SMK) students. Both types of schools have distinctive characteristics. Senior High School focuses more on continuing education, while Vocational School places greater emphasis on education that prioritizes the readiness of its graduates to work. Materials and methods. Quantitative descriptive approach is employed in this study, with high school and vocational school students as the research sample. The Interpersonal Communication Competence Scale (ICCS) is the research tool used in this study. Results. Based on the research findings, it is clear that there are differences in the results of interpersonal communication skills between high school and vocational school students compared to the outcomes of implementing physical education at school. This is evidenced by the results of the independent sample t-test (two-sided p-value) < 0.001. Furthermore, it can also be observed that based on gender (male and female), it is obtained 0.002. Both results have a significance level of <0.05. Conclusions. The findings indicate that vocational school students' interpersonal communication skills have been found to be improved than high school students.